2013
DOI: 10.3109/15419061.2013.791683
|View full text |Cite
|
Sign up to set email alerts
|

IL-11/IL11RA receptor mediated signaling: a web accessible knowledgebase

Abstract: Interleukin-11 (IL-11) is a pleiotropic cytokine that belongs to gp130 family. It plays a signifi cant role in the synthesis and maturation of hematopoietic cells, inhibition of adipogenesis, regulation of embryo implantation, and trophoblasts invasion. Although IL-11 signaling has been described in several biological processes, a centralized resource documenting these molecular reactions induced by IL-11 is not publicly available. In the current study, we have manually annotated the molecular reactions and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Balakrishnan [45] as well as the reaction map of IL-11 signaling pathway, available for visualization at 'NetSlim' (http://www.netpath.org/netslim/) would be very helpful.…”
Section: Biological Sources and Interactions Of Il-11mentioning
confidence: 99%
“…Balakrishnan [45] as well as the reaction map of IL-11 signaling pathway, available for visualization at 'NetSlim' (http://www.netpath.org/netslim/) would be very helpful.…”
Section: Biological Sources and Interactions Of Il-11mentioning
confidence: 99%
“…To examine IL-11 expression in prostate tissues, we carried out IHC analyses indicating a higher IL-11 staining density in PCa tissues compared with normal prostate tissues (Figure 4A ). It has been clearly discussed that biological functions of IL-11 are mediated by binding its specific receptor, IL11Rα [ 17 ]. To examine PCa promotion role of IL-11, we suppressed IL11Rα in PC-3 cells using RNA interference.…”
Section: Resultsmentioning
confidence: 99%
“…Our data based on protein array analyses suggest that stromal LMO2 can stimulate secretion of IL-11 which is a tumor promoting cytokine. IL-11, a member of the IL-6 family, can activate STAT3 signaling downstream via its unique receptor IL11Rα [ 17 ]. Previous studies confirmed serum IL-11 concentration elevation in patients with PCa [ 30 ], breast cancer [ 31 ] and lung cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding IL-11, its upregulation and overexpression in the lungs is usually linked with viral infections, including SARS-CoV-2, and IL-11 induces lung fibrosis and epithelial dysfunction [67]. Hence, IL-11 RA is overexpressed to mediate the cascade of IL-11 function, as discussed below [68] (Figure 1), Table 1.…”
Section: Discussionmentioning
confidence: 97%